Literacy's beginnings : supporting young readers and writers - McGee, Lea M.; Richgels, Donald J. (Boston : Allyn and Bacon, 1996)
The Fifth Edition of Literacy's Beginnings offers an integrated approach to reading and writing instruction keyed to the five typical developmental stages through which most children pass: the IRA/NAEYC phases of literacy. Two of Our Reviewers Sum It Up Best! (3z(BThis is the only book I have considered using for this course for the following reasons:(1) It emphasizes holistic, student-centered, and constructivist understandings and practices; (2) It has a focus on early literacy learners $1 (Band does not try to cover the entire elementary spectrum; (3) It is comprehensive, well written, and uses an integrated approach to the language arts and literacy instruction.(3y $1 (BTuenis Donk, Hope College (3z(BWhat impresses me is the insights the authors have to children, to literacy practices and to early literacy development. The book is filled with rich examples of children$1 (Bs work.(3y $1 (BSheila G. Cohen, SUNY Cortland Lea McGee and Donald Richgels have set the standard in this new edition by clearly and simply explaining the issues addressed in Reading First and Early Reading First legislation that affect the reading instruction of young children. Without question, this text will be the most talked about resource for prospective and current teachers of children from birth to age eight. Take a Peak inside the New Edition! Assessment coverage at the end of many of the chapters includes assessment tasks that are relevant to the level of literacy development discussed in the chapter. Appendices includes practical assessments readily available for use in the classroom. Differentiated Instruction feature offers suggestions on how to modify instruction for all students. ELL coverage includes suggestions on how to specifically modify instruction for ELLs. Biography Lea M. McGee is the Marie Clay Chair of Reading Recovery and Early Literacy at The Ohio University. Donald J. Richgels is a professor at Northern Illinois Universitys
Includes bibliographical references and indexes.
Keywords: Reading (Early childhood) -- United States; anguage arts (Early childhood) -- United States; Literacy -- United States